The Effectiveness of Learning Arabic Through Image Media for Grade VIII Students at MTs Plus Baitussalam Banyuwangi - Furoidah, Asni; Rosa, Amellina Julya (UAS PRESS, 2025)
Arabic is a foreign language that is difficult to learn, moreover one's ability to speak Arabic is supported by good mastery of Arabic vocabulary, therefore collaboration is needed so that the process of these activities can spark the success expected by educators. Learning media is a tool or intermediary that is very appropriate for teachers to use in the process of delivering lessons to students. In other words, the application of instructional media is an effective way for educators to teach, one of which is by using media images, because in addition to helping the smooth delivery of material it also helps so that material explanations from teachers no longer use only the lecture model. The implementation of this research aims to determine the effectiveness of learning Arabic to improve the mufrodat mastery of class VIII students at MTs Plus Baitussalam Banyuwangi. The method used is a qualitative research. The results of this study prove that the use of media images can provide students' understanding, attract students' interest and encourage students' enthusiasm in learning Arabic. This identifies that the use of media images is an effective way, because it can help create an active classroom atmosphere so that students can learn optimally.